Interception, Stemflow and throughfall in a Eucalyptus hybrid Plantation - George, M. (Indian Forester, 1978)
Investigation and interception of precipitation, stemflow and throughfall were carried out for a period of one year in a Eucalyptus hybrid plantation of age 6 years and density 1658 trees/ha in the demonstration Area of F.R.I. & Colleges, New Forest, Dehra Dun. The total stemflow and throughfall over the year accounted for 7.60% (127.2 mm) and 80.75% (13497 mm) of the total rainfall (1671. 7 mm) respectively while only 11.65% (1948 mm) was intercepted by the canopy. The interception loss was 8% to 14% and 19% to 39% of the annual precipitation for rainy season and witer months respectively. The highest interception was recorded in October, the month, which had the lowest rainfall while the lowest interception was recorded in July and August, the months which had the highest rainfall (544.0 mm and 423.7 mm) The average stemflow per tree per year increases with increasing diameter on a unit area basis the amount of stemflow calculated from the sample trees and that of throughfall from sample troughs accounted 1,272.000 litres (kg/ha/year) and 13,497.000 litres (kg/ha/year) respectively. E. hybrid couducts more water as stemflow and throughfall, when compared with other species like sal, teak, chir and khair.